Influence of undefined modes of movement on instantaneous redistribution of normal reactions of quarry dump truck tires - Dadonov Mikhail (EDP Sciences, 2021)
Reducing the costs of rock transportation in mining is one of the most important tasks. One of the reserves for solving this issue is a more complete use of the service life of quarry dump trucks tires, since their operation takes place in heavy mining and climatic conditions and this significantly reduces the life of tires. The life of tires depends on many factors: speed of movement, compliance with the recommended air pressure in the tire, ambient air temperature, but the main thing is the change in the normal load on the wheel, which depends on the redistribution of the quarry dump truck weight in case of non-linear movement and on the longitudinal profile of the quarry road. In real conditions, the quarry dump truck moves unevenly due to the complexity of the road - either braking or acceleration occur. This article allows you to evaluate the impact of non-linear modes of quarry dump truck movement on the instant redistribution of normal tire reactions and take into account peak loads on wheels during acceleration and braking in the regular cycle. This will allow you to control the load on the tires directly by cargo amount in the quarry dump truck and thereby increase the life of the tires and their reliability, as well as reduce the cost of transporting the rock mass in real operating conditions.